2021
DOI: 10.1038/s41598-021-89747-7
|View full text |Cite
|
Sign up to set email alerts
|

The novel immune-related genes predict the prognosis of patients with hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) is one of the main causes of cancer deaths globally. Immunotherapy is becoming increasingly important in the cure of advanced HCC. Thus it is essential to identify biomarkers for treatment response and prognosis prediction. We searched publicly available databases and retrieved 465 samples of genes from The Cancer Genome Atlas (TCGA) database and 115 tumor samples from Gene Expression Omnibus (GEO). Meanwhile, we used the ImmPort database to determine the immune-related genes as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…Likewise, the peculiar contribution of long non-coding RNA (IARlncRNA) can also not be excluded. To date, several prognostic signatures involving autophagy-related (AR) and immune-related (IR) genes have been shown [ 24 , 25 , 26 ], and some have even attempted to combine them with lncRNAs [ 27 , 28 ]. However, to date, no combinatorial signature utilizing IR, AR and lncRNAs has been shown.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, the peculiar contribution of long non-coding RNA (IARlncRNA) can also not be excluded. To date, several prognostic signatures involving autophagy-related (AR) and immune-related (IR) genes have been shown [ 24 , 25 , 26 ], and some have even attempted to combine them with lncRNAs [ 27 , 28 ]. However, to date, no combinatorial signature utilizing IR, AR and lncRNAs has been shown.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, MAT2A can produce SAM, which trimethylates the promoter of ACSL3, leading to ACSL3 upregulation and ferroptosis resistance in gastric cancer [71]. Consistent with these insights, many bioinformatics analyses have reported that ACSL3 can be used to predict the prognosis of various cancers [129][130][131][132][133].…”
Section: Fatty Acidsmentioning
confidence: 94%
“…What's more, TDT was highly associated with tumor vascular invasion and recurrence [ 12 ] and could be regarded as a reliable predictor of sorafenib's therapeutic effect [ 7 ], suggesting that TDT might have a significant relationship with the cancer immune status. Furthermore, immunotherapy is becoming the new standard of treatment for advanced stages, considering its increasing use worldwide to treat HCC patients, although the inadequate immune response has been a growing concern [ 13 ]. However, the association between TDT-related genes (TDTRGs) and immune-related genes (IRGs) and the value of their combination in predicting the prognosis of HCC patients remains unclear.…”
Section: Introductionmentioning
confidence: 99%